Chemical Physical Analysis of River Water Quality in Padang Panjang City - Resti Fevria; Abdul Razak; Eni Kamal; Isril Berd; Edwin Edwin (Science and Environmental Journal for Postgraduate, 2022)
Rivers are bodies of water that are elongated on the earth's surface that are naturally formed, ranging from small ones upstream to large downstream ones. In Padang Panjang City, 10 rivers flow, 6 rivers in West Padang Panjang District, and 4 rivers in East Padang Panjang District. Data from the analysis of river water quality in Padang Panjang City was obtained from secondary data, namely data from river water quality tests conducted by the Padang Panjang City Environment Service in March 2021 and from various other official sources such as journals and articles. The value of water quality in Padang Panjang City, in general, meets the Quality Standards based on PP No. 82/2001, but there are several sources whose values are below the established Quality Standards. The use of surface water for various activities according to water quality standards using physical, chemical, and biological parameters can be grouped into several parts, including human consumption, water recreation, fisheries, industry, and agriculture.